Properties and characterization of starch as a natural binder: A brief overview - N.A. Mohd; M.H.M. Amini; M.N. Masri (Universiti Malaysia Kelantan, 2016)
This paper was reviewed about the properties and characterization of starch as a natural binders. Starch is one of the most abundant organic compounds and applied as a binder. The efficiency of binder are affected by the characteristic and properties of starch. The characteristics of starch are determined by the biological origin. Starch is composed of D-glucose in polysaccharides and it was isolated from leaves, stems, tubers, seeds, and roots of higher plants where it serves as an energy reserve. This review concentrates the several types of characterization which are structural properties, morphology properties, viscosity and functional group of starch. The X-ray diffraction result shows that the relative crystallinity decreased for modified starch compared with native starch while scanning electron microscope shows the modified starch slightly has rough surface compared with native starch. Nowadays, the concern on eco-environmental issues is increasing and this review has shown that starch is eco-environmental friendly binder that can be used in various application.